The Effect of Environmental Performance and CEO Gender on Carbon Emission Disclosure with Leverage as a Moderating Variable - Nadia Saputri; Muhammad Faisal Hakim; Zahra Valizadeh Dizaj (Journal of Applied Accounting and Sustainable Finance, 2026)
Purpose – This study aims to obtain empirical evidence on the influence of environmental performance and CEO gender on carbon emission disclosure, with leverage as a moderating variable. Design/methodology/approach – This study uses quantitative research. The sample in this study consists of 66 companies in the basic materials sector listed on the Indonesia Stock Exchange from 2022 - 2024. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. Findings – The results of this study found that Environmental Performance has a negative and statistically insignificant effect on Carbon Emission Disclosure, while CEO Gender has a negative and statistically insignificant effect on Carbon Emission Disclosure, and Leverage has a negative and statistically insignificant effect on Carbon Emission Disclosure. Furthermore, Environmental Performance does not strengthen the effect of Leverage on Carbon Emission Disclosure, while CEO Gender strengthens the effect of Leverage on Carbon Emission Disclosure. Research limitations/implications – This study discusses Carbon Emission Disclosure and other factors such as Environmental Performance, CEO Gender, and Leverage, focusing on the basic materials sector. These results highlight the importance of executive characteristics under financial constraints and imply that voluntary environmental disclosure in Indonesia remains weak without stronger regulatory enforcement. They contribute to the environmental accounting literature by providing empirical evidence on the interaction between financial pressure and top management characteristics. They also offer policy implications for strengthening the mandatory carbon disclosure framework in emission-intensive sectors. JEL : Q56, M14, G34